EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL WITH WORKSHEET ASSISTED ON STUDENTS' CRITICAL THINKING ABILITY - Rahayu, Satutik; Verawati, Ni Nyoman Sri Putu; Islamiah, Andi Fatimatul (IKIP Mataram, 2019)
This research aims to know the effectiveness of the learning problem based learning model assisted worksheet for the critical thinking ability of physics students of grade X SMAN 1 Lingsar. This was an experiments research that using design research Posttest-Only Control group Design. The population in this research were the whole grade X SMA Negeri 1 Lingsar in academics year 2016/2017. Sampling taken with using cluster random sampling technique with the students of class X MIA.A as experiment class and X MIA.D as control class. Research hypothesis was analysis with the t-test for one party (the party right). Based on the hypothesis test results obtained tcount> ttable at significance level of 5%, then it can be inferred that the model of learning problem based learning assisted work sheet effective for critical thinking ability of physics students SMAN 1 Lingsar.